THE CONDUCT OF THE ḤAJJ IN MALAYSIA AND ITS ECONOMIC IMPACT ON THE SOCIETY: 1963-2005 - Sharifah Ismail; Haslinda Hasan (Journal of Islamic, Social, Economics and Development, 2020)
Ḥajj, the annual pilgrimage to Makkah is the fifth and last fundamental pillar ofIslam and is mandatory for Muslims who are physically and financially able to make thepilgrimage. Therefore, the ḥajj is closely associated with economic system as it is a prerequisitein fulfilling the ḥajj. The ḥajj institution in Malaysia under the direction of Lembaga TabungHaji, particularly from 1963 to 2005, contributed to a series of developments and progress ofthe nation’s economy. With the progress made in the pilgrimage management particularlyduring the period, the ḥajj institution under the direction of Tabung Haji has experienced rapidexpansion and reforms thus had direct economic implications on the pilgrims and the ḥajjinstitution itself. This paper highlights the conduct of ḥajj from Malaysia with special referenceto the roles of Tabung Haji and the ḥajj that have caused in very important economicconsequences for all aspects of the pilgrims and pilgrimage institution itself. The researcheradopts a qualitative method that enables her to analyze and assess the material andinformation collected from the primary and secondary sources. This study concluded thatTabung Haji had considerably contributed to the significant changes in Malaysian ḥajjinstitution and led to transformative economic impacts on the ḥajj institution and thecommunity as a whole.